An Introduction to the Blue Humanities - Mentz, Steve (New York Routledge, 2023)
"An Introduction to The Blue Humanities is the first textbook to explore the many ways humans engage with water, utilizing literary, cultural, historical, and theoretical connections and ecologies to introduce students to the history and theory of water-centric thinking. Comprised of multinational texts and materials, each chapter will provide readers with a range of primary and secondary sources, offering a fresh look at the major oceanic regions, salt and freshwater geographies, and the physical properties of water that characterize the Blue Humanities. Each chapter engages with carefully-chosen primary texts, including frequently-taught works such as Herman Melville's Moby Dick, Samuel Taylor Coleridge's The Rime of the Ancient Mariner, Homer's The Odyssey, and Luis Vaz de Camões' The Lusiads, to provide the perfect pedagogy for students to develop an understanding of the Blue Humanities chapter by chapter. Readers will gain insight into new trends in intellectual culture and the long histories of humans thinking with water, ranging across the many coastlines of the World Ocean to Pacific clouds, Mediterranean lakes, Caribbean swamps, Arctic glaciers, Southern Ocean rainstorms, Atlantic groundwater, and Indian Ocean rivers. Providing new avenues for future thinking and investigation of the Blue Humanities, this volume will be ideal for both undergraduate and graduate courses engaging with the environmental humanities and oceanic literature"--
Preface : bodies of water -- A poetics of planetary water -- Blue humanities thinking -- The vast Pacific -- The roaring south -- The connected ocean -- Surrounded by land -- In the Caribbean -- Northern lights -- The tornadoed Atlantic -- Conclusion : touching moisture.
Includes bibliographical references and index.
Keywords: Ecology; Literature; Philosophy; Humanities